Abbas Ibn Firnas's contribution in aviation - Mohamed Ali Suliman, Suliman Mohamed; Mirghani, Mohamed Elwathig Saeed (IIUM Press, 2011)
Abros Ibn Fimas (810-887 CEl, ",:ho came 10 Cordoro from Baghdad 10 teach music Iheory :lIthe court of Abd al·Rahman 111. Ib" Firnas had workro in many lields, such as. chemislry, physics, aslronomy, and as a poc!. He deSigned a water clock, he worked 10 impw\'e the way glass was madc, have worked on eyeglaS5es to hdp those wilh weake vision. He devised a way 10 CUI very hard quar11~ or T<lck crystal, and fubricated a mechanical model to show Ihe motions of planets and stars. In 875 CE, Ibn Firnas constructed a glider. and launched himself into the air. The /light was successful. and was viewed by a crowd of people. As an experimental vehicle. However, the landing was bad.The objective of this cMpler is 10 describe, compare and discuss Ibn Abbas's Experimental theory in avialion science. The significance oflhis chapler to show how far he contributed in aviation. Comparison method had been used 10 evaluale Abbas's Ihcory, The basic flight theory had been used as measuremem. The chapter explores the contribution of Abbas Ibl> rlfnas in aviation.The methodology of this chapter uses library based source such as books. journals and other relavant sourc